Priming of pyrogenic C (biochar) mineralization by dissolved organic matter and vice versa. (March 2019) - Zimmerman, Andrew R.; Ouyang, Lei
Abstract: Due to expected changes in fire frequency and the potential of using pyrolyzed biomass (biochar) amendments to increase soil C storage, there is a need for better ability to predict pyrogenic C (pyC) longevity in soil and its effects on native soil C stability. However, C mineralization from biochar/soil mixtures has been shown to vary greatly and both 'positive' and 'negative' priming (increased and decreased mineralization of native C, respectively) following biochar amendments have been observed. To better understand the interactions that influence mineralization of pyC and native soil C, bagasse (sugar cane residues) and bagasse biochar pyrolyzed at 300 and 650 °C were incubated in sand over 144 d with soil microbes and dissolved organic matter (DOM) substrates of high and low reactivity (sucrose and humic acid: HA, respectively). Mineralization of particulate and dissolved C was quantified based upon the distinct C isotopic signature of CO2 evolved from each source. Negative priming of bagasse-C mineralization by sucrose (−9.3% cumulative C mineralized) and pyC mineralization by HA (−29 and −68% for low and high temperature biochar, respectively) pointed to the mechanism of ' substrate switching ', i.e. cases in which added DOM was of greater or similar lability to the particulate OM present. In contrast, positive priming of bagasse mineralization by HA (+77%) and pyC mineralization by sucrose (+271 and 614% for low and high temperature biochar, respectively), was attributed to the mechanisms of soil conditioning (creation of an environment more favourable to microbial growth) and co-metabolism, respectively. Inversely, presence of all the particulates enhanced the mineralization of sucrose (by 8, 58 and 91% for bagasse and low and high temperature biochar, respectively), suggesting a soil conditioning mechanism. In contrast, the biochars had little effect on HA mineralization, likely because of their similar inherent stability and chemistry. These results show that DOM and pyC mineralization in soil is interactive and varies with OM type. Furthermore, the priming observed could be attributed to different mechanisms in different cases, the long term effect of which would likely be greater soil C sequestration than predicted by simple degradation models. Graphical abstract: Image 1 Highlights: Positive priming of pyC (biochar) mineralization by sucrose was attributed to 'co-metabolism'. Negative priming of biomass-C by sucrose and pyC by humic acid was caused by 'substrate switching'. Biochar had little effect on humic acid-C mineralization. Priming via pyC addition may cause short term soil C losses, but addition gains in the long term.